A Novel High Capacity Positive Electrode Material with Tunnel‐Type Structure for Aqueous Sodium‐Ion Batteries. Issue 22 (6th August 2015) - Wang, Yuesheng; Mu, Linqin; Liu, Jue; Yang, Zhenzhong; Yu, Xiqian; Gu, Lin; Hu, Yong‐Sheng; Li, Hong; Yang, Xiao‐Qing; Chen, Liquan; Huang, Xuejie
Abstract : Aqueous sodium‐ion batteries have shown desired properties of high safety characteristics and low‐cost for large‐scale energy storage applications such as smart grid, because of the abundant sodium resources as well as the inherently safer aqueous electrolytes. Among various Na insertion electrode materials, tunnel‐type Na0.44 MnO2 has been widely investigated as a positive electrode for aqueous sodium‐ion batteries. However, the low achievable capacity hinders its practical applications. Here, a novel sodium rich tunnel‐type positive material with a nominal composition of Na0.66 [Mn0.66 Ti0.34 ]O2 is reported. The tunnel‐type structure of Na0.44 MnO2 obtained for this compound is confirmed by X‐ray diffraction and atomic‐scale spherical aberration‐corrected scanning transmission electron microscopy/electron energy‐loss spectrum. When cycled as positive electrode in full cells using NaTi2 (PO4 )3 /C as negative electrode in 1m Na2 SO4 aqueous electrolyte, this material shows the highest capacity of 76 mAh g −1 among the Na insertion oxides with an average operating voltage of 1.2 V at a current rate of 2 C. These results demonstrate that Na0.66 [Mn0.66 Ti0.34 ]O2 is a promising positive electrode material for rechargeable aqueous sodium‐ion batteries. Abstract : Tunnel‐type Na0.66 [Mn0.66 Ti0.34 ]O2 is successfully designed and synthesized as a positive electrode material for aqueous sodium‐ion batteries. It shows a high reversible capacity of ≈76 mAh g −1 at a current rate of 2 C with an average voltage of 1.2 V vs. NaTi2 (PO4 )3 (NTP). The aqueous full‐cell demonstrates excellent cycle performance with small capacity decay after 300 cycles.